Estimating the cutting force when skiving with a radius cutter; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Filippov A. V. Andrey Vladimirovich (Innovative technologies for producing and machining materials in mechanical engineering, 2015)
Title screen